(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
Denise Di Santos reflects on her journey in Lambe-Lambe Theater, highlighting family and educational influences, especially from ABTB and her mother. She explores the evolution of theatrical form, addressing themes such as birth and sexuality. The text underscores creativity as a response to emotional and cultural needs, emphasizing the adaptation of theater to honor different cultures. Denise also emphasizes the importance of resilience and generosity in the artistic community, highlighting the educational and cultural transformation facilitated by Lambe-Lambe Theater.